“Those Conversations in My Experience Don’t Go Well”: A Qualitative Study of Primary Care Provider Experiences Tapering Long-term Opioid Medications - Kennedy, Laura C (Pain Med, 2018)
OBJECTIVE: Given the risks of long-term opioid therapy, patients may benefit from tapering these medications. There is little evidence to guide providers’ approach to this process. We explored primary care providers’ experiences discussing and implementing opioid tapering with patients on long-term opioid therapy. DESIGN: Qualitative study using six semistructured, in-person focus groups. SUBJECT: Primary care providers (N = 40). SETTING: Six academically affiliated primary care clinics in university, urban safety net, and Veterans Health Administration medical centers in Colorado. METHODS: Focus groups were audio-recorded, transcribed, and analyzed using a mixed inductive-deductive approach in ATLAS.ti. Emergent themes were identified through an iterative, multidisciplinary team-based process. RESULTS: We identified 1) strategies for identifying candidates for opioid tapering, 2) barriers to opioid tapering, and 3) facilitators of opioid tapering. Strategies for identifying candidates for opioid tapering included evidence of high-risk behavior, serious adverse events, opioid-related side effects, and patient preference. Barriers included the providers’ emotional burden, inadequate resources, and a lack of trust between patient and provider. Facilitators of opioid tapering included empathizing with the patient’s experience, preparing patients for opioid tapering, individualizing implementation of opioid tapering, and supportive guidelines and policies. CONCLUSIONS: While discussing and implementing opioid tapering present significant challenges, primary care providers described key facilitators. These findings suggest a need to develop and test the effectiveness of resources to support patient-centered opioid tapering and locally developed policies to support and standardize providers’ approaches to opioid prescribing.